Characterizing the Foreshock, Main Shock, and Aftershock Sequences of the Recent Major Earthquakes in Southern Alaska, 2016–2018 - Bukchin, B. G.; Fomochkina, A. S.; Kossobokov, V. G.; Nekrasova, A. K. (Frontiers in Earth Science, 2020)
For each of three major M ≥ 7.0 earthquakes (i.e., the January 24, 2016, M7.1 earthquake 86 km E of Old Iliamna; the January 23, 2018, M7.9 earthquake 280 km SE of Kodiak; and the November 30, 2018, M7.1 earthquake 14 km NNW of Anchorage, Alaska), the study considers characterization of the foreshock and aftershock sequences in terms of their variations and scaling properties, including the behavior of the control parameter η of the unified scaling law for earthquakes (USLE), along with a detailed analysis of the surface wave records for reconstruction of the source in the approximation of the second moments of the stress glut tensor to obtain integral estimation of its length, orientation, and development over time. The three major earthquakes at 600 km around Anchorage are, in fact, very different due to apparent complexity of earthquake flow dynamics in the orogenic corner of the Pacific and North America plate boundary. The USLE generalizes the classic Gutenberg-Richter relationship taking into account the self-similar scaling of the empirical distribution of earthquake epicenters. The study confirms the existence of the long-term periods of regional stability of the USLE control parameter that are interrupted by mid- or even short-term bursts of activity associated with major catastrophic events.